Land, People, Space, and Place: Constructing a Decolonized Reparative Understanding of the Biblical Creation Myth Through Dialogue Between the Hebrew Bible and Haudenosaunee Creation Stories - Mhlanga, Thandazani (Stellenbosch : Stellenbosch University, 2026)
Thesis (PhD)--Stellenbosch University, 2026.